The gradual erosion of the social security function of customary land tenure arrangements in lineage-based societies - Jean-Philippe Platteau (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Customary rules governing access to land and other natural resources in village societies have characteristics that allow them to fulfil social security functions and achieve equity objectives. This is true of both common-property resources and land parcels held under individualized tenure. However, when land pressure increases under the combined influences of population growth and market integration, a shift occurs from extensive to intensive resource use patterns. As a result, the efficiency costs of erstwhile equity- and insurance-oriented arrangements rise, thus forcing them to evolve significantly. In particular, land tenure arrangements undergo a major transformation towards more individualized forms with the consequence that property rights in land are increasingly defined without regard for equity and insurance concerns.
Keywords: O13; O17; Q15; 330; land tenure; informal insurance; equity; common property; Bodenrecht; Allmenderessource; Theorie